Uji Efektifitas Getah Jarak Pagar (Jatropha Curcas) Sebagai Obat Pengganti Antiseptik Kimia - Hajiriah, Titi Laily; Intan, Putri Komala (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this study was to investigate the effectiveness of healing in cut wounds by administering Jatropha curcas in a gel formulation that is effective in healing cuts of tested animals. The sap was obtained by breaking Jatropha curcas (Jathropha curcas), stored and then was formulated into a gel with a sap concentration of 0%, 8%, 16%. The wound healing effect test was carried out on mice by injuring 15 mm and was smeared every day with Jatropha gum gel and compared to Betadine until the wound healed. The result of the study showed that the gel formula with a concentration of 0% healed wounds on the 10th day, an concentration of 8% healed the wounds on the 8th day, and a concentration of 16% on the 6th day, whereas Betadine 10% as a comparison of mice died. Thus, from the research conducted it can be concluded that Jatropha curcas in the form of gel preparations can provide the best healing effect at a concentration of 16% with the fastest wound healing time of 6 days.